2018
DOI: 10.3748/wjg.v24.i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intestinal microbiota and ulcerative colitis: Mechanisms and clinical application of probiotics and fecal microbiota transplantation

Abstract: Ulcerative colitis (UC) is an inflammatory disease that mainly affects the colon and rectum. It is believed that genetic factors, host immune system disorders, intestinal microbiota dysbiosis, and environmental factors contribute to the pathogenesis of UC. However, studies on the role of intestinal microbiota in the pathogenesis of UC have been inconclusive. Studies have shown that probiotics improve intestinal mucosa barrier function and immune system function and promote secretion of anti-inflammatory factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
288
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 485 publications
(366 citation statements)
references
References 93 publications
10
288
0
11
Order By: Relevance
“…We found through functional prediction that the relative abundance of intestinal flora was significantly different in infectious diseases. Further analysis of the species composition of the different pathways revealed that Lachnospiraceae contributed the most to L-lysine fermentation to acetate and butanoate, consistent with previous studies 50 . This indicated that Lachnospiraceae may be the key bacteria for the effectiveness of FMT.…”
Section: Analysis Of Short-chain Fatty Acids (Scfas) By Lc-mssupporting
confidence: 89%
“…We found through functional prediction that the relative abundance of intestinal flora was significantly different in infectious diseases. Further analysis of the species composition of the different pathways revealed that Lachnospiraceae contributed the most to L-lysine fermentation to acetate and butanoate, consistent with previous studies 50 . This indicated that Lachnospiraceae may be the key bacteria for the effectiveness of FMT.…”
Section: Analysis Of Short-chain Fatty Acids (Scfas) By Lc-mssupporting
confidence: 89%
“…The gut microbiota is involved in the development of intestinal inflammation and UC. Therefore, microbial manipulation could be an alternative therapeutic approach for UC (47). FMT may serve as an effective treatment strategy for UC, as it is able to correct the altered gut microbial community and restore microbial homeostasis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Cell shedding represents an important host physiological response which ensures continuity of the intestinal epithelial layer despite continuous replacement of intestinal epithelial cells every 3-5 days [11]. Crucially, intestinal inflammation is correlated with elevated or 'pathological' cell shedding, which is also correlated with altered microbiota profiles [12][13][14]. Previous studies have indicated that antibiotic usage, and antibiotic-induced microbiota perturbations, particularly in infancy, are linked to increased risk of developing inflammatory disorders in later life [15].…”
Section: Introductionmentioning
confidence: 99%